เพลงกันตรึมเกี่ยวกับประเพณีแซนโฎนตาและอัตลักษณ์ของผู้พูดภาษาเขมรถิ่นไทยในอีสานตอนใต้ของไทย - หงษ์ทอง ดิเรก (Journal of Letters, 2016)
ผู้พูดภาษาเขมรถิ่นไทยในอีสานตอนใต้ของไทยมีวัฒนธรรมหลายอย่างที่แสดงถึง อัตลักษณ์ของกลุ่ม วัฒนธรรมที่รู้จักกันแพร่หลายที่สุดคือเพลงกันตรึม เพลงกันตรึมทั่วไปมักถ่ายทอดด้วยภาษาเขมรถิ่นไทยและมีเนื้อหาเกี่ยวกับความรัก เรื่องราวสุขทุกข์ในชีวิต และการสั่งสอนจริยธรรม แต่เมื่อราว พ.ศ. 2545 เป็นต้นมาได้เกิดเพลงกันตรึมกลุ่มใหม่ที่ยังคงถ่ายทอดด้วยภาษาเขมรถิ่นไทย แต่มีเนื้อหาเกี่ยวกับประเพณีแซนโฎนตาซึ่งเป็นประเพณีที่เชิดชูหัวใจของวัฒนธรรมเขมรถิ่นไทย บทความนี้มุ่งค้นหาอัตลักษณ์ของผู้พูดภาษาเขมรถิ่นไทยในข้อมูลพิเศษดังกล่าวและศึกษาถึงปัจจัยที่มีอิทธิพลต่อการผลิตเพลงกลุ่มนี้และต่อการนำเสนออัตลักษณ์ในเพลง ผลการวิจัยเผยถึงอัตลักษณ์อันหลากหลายของชนกลุ่มน้อยชาติพันธุ์เขมรในบริบทสังคมไทย กระแสท้องถิ่นนิยมที่กระตุ้นการผลิตสื่อชาติพันธุ์เพื่อร่วมปกป้องวัฒนธรรมของกลุ่มที่อยู่ในภาวะวิกฤต และปัจจัยด้านภูมิศาสตร์ ประวัติศาสตร์ เศรษฐกิจ วัฒนธรรม การเมืองระดับท้องถิ่นและระดับชาติที่มีอิทธิพลต่อการประกอบสร้างอัตลักษณ์ Kantruem Songs Concerning Saen Don Ta Tradition and Identity of Northern Khmer Speakers in the Southern Part of Northeastern Thailand Northern Khmer speakers in the southern part of Northeastern Thailand own several cultural components which express their group identity. The most well-known one is Kantruem song. General Kantruem lyrics, usually composed in Northern Khmer language, are about love, happiness and sorrow, and moral instruction. From approximately 2002 onwards, have emerged the inexperienced Kantruem lyrics, still in Northern Khmer language, concerning Saen Don Ta, the tradition which highlights the core of Northern Khmer culture. This paper aims at examining Northern Khmer speakers’ identities through these special data, and the factors influencing the production of these new lyrics and the identifications. The study reveals various identities of ethnic Khmer minority dwelling in Thailand; the localism which has influenced the ethnic media production for the collaborative protection of the Northern Khmer speakers’ culture in crisis; and many factors influencing the identifications which comprise of geographical, historical, economic, cultural, and regionally and nationally political factors.